Indigenous nationhood and herring governance: strategies for the reassertion of Indigenous authority and inter-Indigenous solidarity regarding marine resources. (March 2019) - von der Porten, Suzanne; Corntassel, Jeff; Mucina, Devi
The modern-day reinvigoration of individual Indigenous nations around the world is connected to broader simultaneous movements of Indigenous nationhood worldwide. The origins, implications, philosophies, and diversities of Indigenous resurgences and resistances continue to be discussed in the growing body of literature on Indigenous governance. This article builds on these discussions by focusing on the applied tools and strategies of Indigenous resurgence. In the context of the Pacific herring fishery in British Columbia, Canada, this research explores the strategies and tools used by three Indigenous coastal nations to apply pressure on the colonial government to abdicate its asserted authority over herring governance. Motivated by a time-honored relationship to herring, we discuss how these Indigenous nations have strategized to try to regain authority over herring governance to protect species and Indigenous access to the fishery. We then discuss this ocean-based resurgence in the context of global Indigenous movements for the reassertion of self-determining authority.